MODERN METHODS OF FORMING PEDAGOGICAL COMPETENCIES IN FUTURE TEACHERS - Dildora Azizovna Xolbayeva (Bright Mind Publishing, 2025)
The formation of pedagogical competencies in future teachers is a crucial aspect of modern education in Uzbekistan. This study explores contemporary methods employed in teacher training institutions to develop essential pedagogical skills. The paper analyzes various approaches, including innovative teaching methodologies, digital tools, and competency-based education models. It examines the impact of these methods on student teachers’ preparedness for professional practice and their ability to adapt to evolving educational standards. By reviewing existing literature and empirical data, the study highlights the effectiveness of current pedagogical strategies and identifies areas for further improvement. The findings contribute to the ongoing discussion on enhancing teacher education programs in Uzbekistan to align with global educational trends and national development goals.
Keywords: Pedagogical competencies, teacher education, Uzbekistan, digital tools, competency-based learning, professional development, innovative teaching methods.